Survei Hasil Belajar PJOK Masa Pandemi Covid-19 di SMK Negeri 1 Suwawa - Dai, Aswan; Hadjarati, Hartono; Haryanto, Arief Ibnu (Ilmu Olahraga, 2022)
The process of Physical Education, Sports and Health (PJOK) during the Covid-19 pandemic will certainly change the pattern of learning that is usually offline to online. This study aims to survey the learning outcomes of Physical Education, Sports, and Health (PJOK) at SMK Negeri 1 Suwawa. This research is a qualitative research with data collection techniques by observation and also interviews conducted in March 2021. The sample of this study amounted to 58 people consisting of 1 teacher of Physical Education, Sports, and Health (PJOK) and also class X Computer Engineering students. and the Network (TKJ) totaling 57 students. The results of this study revealed that in learning Physical Education, Sports, and Health (PJOK) during the Covid-19 pandemic at SMK Negeri 1 Suwawa it was less effective due to several factors such as the environment, internet network conditions, and also the economic conditions of students who were poor. has no strings.